UJI SENSITIVITAS ISOLAT Aeromonas hydrophila DARI IKAN GURAMI (Osphronemus gourame) TERHADAP BEBERAPA ANTIBIOTIK - , PUTU CRI DEVISCHA G, Prof. drh. Kurniasih, MVSc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Aeromonas hydrophila is a kind of opportunistic pathogens bacteria in cultivation fish and causes âMotile Aeromonas Septicaemiaâ disease. This disease can cause mortality and impact on economics. This research aimed to detection the sensitivity rate of Aeromonas hydrophila that isolated from gouramy (Osphronemus gouramy) to some antibiotics. Three isolates of Aeromonas hydrophila were tested with Kirby-Bauer disk diffusion method using Mueller Hinton Agar as the media. The antibiotic used are ampicillin, doxycycline, enrofloxacine, erythromycin, and gentamicine, were put on the surface of Aeromonas hydrophila culture. After being incubated at 28ÂºC for 24 hours, the diameter of inhibition zone that formed around the disk were measured and compared to the Kirby-Bauer standard. Based on the zone of inhibition around the disk that formed, then Aeromonas hydrophila of the three isolat showed the best sensistivity on enrofloxacine and gentamicine.